Implementation of Visual Audio Media in Increasing Learning Interest of Students in SD IT Luqman Al Hakim - Ni’mal Chitam (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to increase students' interest in learning thematic learning in grade VI elementary schools using audio-visual media. This research is a classroom action research (PTK) which is carried out in three cycles, each cycle consisting of stages planning, implementing, observing, and reflecting. The subjects of this research are students of class VI SDIT Luqman Al Hakim Kudus for the 2020/2021 academic year totaled 19 students. Data collection techniques using observation and test. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the implementation of audio visual media can increase student interest in thematic learning in class VI SDIT Luqman Al Hakim Kudus for the 2020/2021 academic year as evidenced by the percentage of interest in learning in cycle I of 37% to 53% in cycle II. And to 89% on cycle 3.